Gamification in Islamic Religious Education: Interactive Learning Innovations to Increase Students' Interest in Learning - Nurul Khatimah; Zahraini Zahraini (Al-Ilmu, 2025)
Students' interest in learning Islamic Religious Education (PAI) tends to be low because the learning method is still predominantly lecture-based and lacks interactivity. This study aims to analyze the effectiveness of gamification as an interactive learning innovation to increase the learning interest of PAI students. A descriptive quantitative approach with a quasi-experimental design was used on 72 junior high school students who were divided into an experimental group (using gamification through Kahoot and Quizizz) and a control group (using conventional methods). The research instrument was in the form of a learning interest questionnaire on a Likert scale and a student involvement observation sheet. The results showed a significant increase in the experimental group, with the average learning interest score increasing by 20.3 points, while the control group only increased by 6.6 points. The results of the paired t-test also showed a significant difference (p < 0.05) in the experimental group. Observations support these findings, where the participation rate of students in the experimental class reached 85%, while in the control group it was only 45%. The findings confirm that gamification is able to create a more interactive, competitive, and fun learning atmosphere, while still internalizing Islamic values. This study recommends the application of gamification as an innovative strategy in PAI learning, although it needs to be adjusted to school infrastructure and student conditions.